End-of-life care in the intensive care unit: A patient-based questionnaire of intensive care unit staff perception and relatives' psychological response. (April 2015) - Hartog, Christiane S; Schwarzkopf, Daniel; Riedemann, Niels C; Pfeifer, Ruediger; Guenther, Albrecht; Egerland, Kati; Sprung, Charles L; Hoyer, Heike; Gensichen, Jochen; Reinhart, Konrad
Background: Communication is a hallmark of end-of-life care in the intensive care unit. It may influence the impact of end-of-life care on patients' relatives. We aimed to assess end-of-life care and communication from the perspective of intensive care unit staff and relate it to relatives' psychological symptoms. Design: Prospective observational study based on consecutive patients with severe sepsis receiving end-of-life care; trial registration NCT01247792. Setting/participants: Four interdisciplinary intensive care units of a German University hospital. Responsible health personnel (attendings, residents and nurses) were questioned on the day of the first end-of-life decision (to withdraw or withhold life-supporting therapies) and after patients had died or were discharged. Relatives were interviewed by phone after 90 days. Results: Overall, 145 patients, 610 caregiver responses (92% response) and 84 relative interviews (70% response) were analysed. Most (86%) end-of-life decisions were initiated by attendings and only 2% by nurses; 41% of nurses did not know enough about end-of-life decisions to communicate with relatives. Discomfort with end-of-life decisions was low. Relatives reported high satisfaction with decision-making and care, 87% thought their degree of involvement had been just right. However, 51%, 48% or 33% of relatives had symptoms of post-traumatic stress disorder, anxiety or depression, respectively. Predictors for depression and post-traumatic stress disorder were patient age and relatives' gender. Relatives' satisfaction with medical care and communication predicted less anxiety ( p  = 0.025). Conclusion: Communication should be improved within the intensive care unit caregiver team to strengthen the involvement of nurses in end-of-life care. Improved communication between caregivers and the family might lessen relatives' long-term anxiety.